Nitrate Reductase Modulation in Response to Changes in C/N Balance and Nitrogen Source in Arabidopsis - Huarancca Reyes, Thais; Scartazza, Andrea; Pompeiano, Antonio; Ciurli, Andrea; Lu, Yu; Guglielminetti, Lorenzo; Yamaguchi, Junji (Plant and Cell Physiology, 2018)
Environmental cues modulate the balance of carbon (C) and nitrogen (N) which are essential elements for plant metabolism and growth. In Arabidopsis, photochemical efficiency of PSII, phosphorylation status and localization of many enzymes, and the level of total soluble sugars were affected by an unbalanced C/N ratio. Since differences in C/N affect these parameters, here we checked whether different sources of N have different effects when a high C/N ratio is imposed. NO3- and NH4+ were separately provided in C/N medium. We investigated the effects on photochemical efficiency of PSII, the level of total soluble sugars and nitrate reductase activity under stressful C/N conditions compared with control conditions. We found that treated plants accumulated more total soluble sugars when compared with control. Photochemical efficiency of PSII did not show significant differences between the two sources of nitrogen after 24 h. The actual nitrate reductase activity was the result of a combination of activity, activation state and protein level. This activity constantly decreased starting from time zero in control conditions; in contrast, the actual nitrate reductase activity showed a peak at 2 h after treatment with NO3-, and at 30 min with NH4+. This, according to the level of total soluble sugars, can be explained by the existence of a cross-talk between the sugars in excess and low nitrate in the medium that blocks the activity of nitrate reductase in stressful sugar conditions until the plant is adapted to the stress.
Keywords: 14-3-3 Proteins; amoniové sloučeniny; Arabidopsis; nitrátreduktasa; Ammonium Compounds; Nitrates; proteiny 14-3-3; dusičnany; Nitrate Reductase; fosforylace; Carbon; uhlík; Nitrogen; Gene Expression Regulation, Plant; regulace genové exprese u rostlin; dusík; Phosphorylation